Analisis pelaksanaan dan penatausahaan belanja modal berdasarkan Permendagri Nomor 77 Tahun 2020 pada Badan Pendapatan Daerah Provinsi Sulawesi Utara - Adyanto; Manossoh, Hendrik; Walandouw, Stanley Kho (Yayasan Widyantara Nawasena Raharja, 2024)
The implementation and administration of expenditure is an essential aspect of regional financial management. Capital expenditure is the acquisition of fixed assets and other assets. It is therefore essential that implementation and administration of expenditure is carried out effectively. The implementation and administration of expenditure is regulated by Regulation of the Minister of Home Affairs Number 77 of 2020. This study will determine how the Regulation of the Minister of Home Affairs Number 77 is implemented and administered in relation to capital expenditure. This study employs a descriptive qualitative research method. We collected data through interviews, observation, and documentation. The data analysis process is carried out by collecting data, which is then processed and described. The results of this study are clear: capital expenditure with a cash advance is not implemented, and expenditure is carried out without a cash advance. Furthermore, the administration of capital expenditure is in accordance with current regulations, starting from the issuance of SPD, SPP LS, SPM LS, SP2D, bookkeeping, and submission of the Treasurer's accountability report at the Regional Revenue Agency of North Sulawesi Province.